EDUCATIONAL PROBLEMS AMONG CHARGES FROM EDUCATIONAL CARE CENTRES (ON THE EXAMPLE OF LUBELSKIE VOIVODESHIP) - Ruszkowska, Marzena Urszula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In times of ongoing changes, schooling and education have become the areas at particular threat since they need to comply with the requirements of time and expectations of both the children and their parents or guardians. Education is perceived as the basic task in the life of each human being, conditioning his or her obtainment of education which determines chances of success in professional activity as well as participation in the social and cultural life. When a child is brought up outside the family environment, thus, in foster custody, the meaning of schooling and education becomes particularly crucial. The research, for the purposes of this publication, was conducted on the territory of Bialski and Krasnostawski districts, which are part of the Lubelskie voivodeship. Its implementation was planned within the framework of the project "Education, levelling developmental and educational deficits deficiencies of children under the care of family-run children's houses homes as well as the educational care centres care and educational institutions (on the example of the selected poviats of the Lublin province)". The method of diagnostic survey as well as individual research study were applied in the following research. Within the range of the survey, not only proprietary questionnaire intended for the dependants brought up at educational care facilities and family-type children’s homes but also interview questionnaire dedicated for counsellors employed at both family and institutional facilities were applied. The individual case studies study of individual cases involved the use of an observation sheet and interviews with coordinators of the researched care and educational centres, directors of family-run children’s houses. The subject of the article reads: educational problems among children from educational care centres. The aim of the research was to determine whether the charges of family and institutional facilities exhibit educational difficulties, how are educational gaps compensated, and what factors affect the proper satisfaction of educational needs? The aim of the research was to determine whether the dependants of both family and institutional facilities display educational difficulties. The author also attempted to answer the question how educational deficiencies are compensated and what factors influence the appropriate satisfaction of educational needs. The analysis of the results allowed to conclude that the foster care pupils display numerous educational deficiencies conditioned by previous educational negligence. The greatest problem for them is the acquisition of knowledge in the field of mathematics. A large group of children participating in the research (over 40%) stated that there are no problems with studying at all. However, contrary to the statements of the dependants, educators and guardians argue that the main problem many dependants face are not only falling behind with the schoolwork and negligence, but also lack of regularity, lack of a learning habit as well as inability to organize learning. Among the indicators determining the proper satisfaction of educational needs the following should be mentioned: location of educational care facilities; willingness and motivation to learn, time devoted to learning, dependants’ age, lack of interest in studying, lack of educational-professional aspirations, lack of patterns connected with learning observed at home as well as pretty low level of intellect.